406 The Combined Effects of Antenatal Inflammation and Betamethasone on Lung Morphometry in a Rat. (October 2012) - Lee, JM; Choi, CW; Lee, HJ; Kim, BI; Lee, JA; Kim, EK; Kim, HS; Choi, JH
Abstract : Aim: To investigate the effects of antenatal maternal glucocorticoids on fetal lung inflammation by determining lung morphology and inflammatory cell influx in bronchoalveolar lavage fluid. Methods: Rat pups were divided into four experimental groups: vehicle (Control; n=18), maternal betamethasone administration (Beta; n=16), intra-amniotic lipopolysaccharide administration (LPS; n=18), or both betamethasone and lipopolysaccharide administration (Beta+LPS; n=20). The changes of lung morphometry were examined on day 5 and 14 and total and differential white cell counts were performed on the bronchoalveolar lavage (BAL) fluid at day 2 and 5. Results: The Beta+LPS group showed marked inhibition of alveolarization, which was characterized by the larger and fewer distal air spaces at day 7 and sustained at day 14. The combination of betamethasone and LPS had significantly larger air spaces than the control, Beta and LPS groups and lower alveolar surface area than the control and LPS groups on day 14. Combination of betamethasone and LPS significantly decreased neutrophil counts in BAL fluid compared with LPS alone group on day 2, but the neutrophil counts were no longer decreased with a delayed clearance of the inflammation (P = 0.041). On day 5, the Beta+LPS group had significantly more neutrophils compared to the LPS group in BAL fluid (P = 0.004). Conclusion: Our results suggest that concurrent exposures of both betamethason and LPS in the fetal lung may modulate inflammatory responses to continal resulting in bronchopulmonary dysplasia.